Pengembangan Backend Aplikasi Kuesioner Evaluasi Kepuasan Proses Belajar Mengajar dan Pelayanan Terhadap Civitas Akademika Berbasis Web di Politeknik Negeri Banyuwangi - Firdaus, Ardian; Agus Priyo Utomo; Alfin Hidayat; Panduardi, Farizqi; Haq, Endi Sailul (Jurnal Informatika dan Komputer, 2025)
Advances in information and communication technology open up new opportunities in the world of education. However, Google Form has limitations in managing questionnaire data, so it hampers the process of evaluating teaching and learning satisfaction and services at Banyuwangi State Polytechnic which is done manually. This research aims to create a web-based questionnaire application to solve the problem. The method used is Agile Software Development with API (Application Programming Interface) using Laravel, focusing on creating a reliable backend system to organize data, process information, and provide a secure API. Laravel and the Agile method were chosen because of its superior features and easy to adjust to changes. This application is expected to improve the quality of satisfaction evaluation, to help summarize data precisely and up-to-date, and to save time and resources in the evaluation process. This application has the potential to overcome the shortcomings of the current evaluation system and provide a better solution. Therefore, it can be concluded that the development of this application can improve the quality of education and services on campus through faster and more precise evaluation.